Predicting Social Anxiety Through Peer Rejection and Fear of Negative Evaluation in Youth - Muñoz, Nayelli; Morales, Luis; Karstensen, Valerie (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This This study aimed to examine the predictive roles of peer rejection and fear of negative evaluation in relation to social anxiety among adolescents in Peru. Methods and Materials: The research employed a correlational descriptive design with a sample of 378 adolescents selected based on the Krejcie and Morgan sampling table. Participants were recruited from public and private secondary schools in Peru using stratified random sampling. Standardized instruments were used to measure the study variables: the Social Anxiety Scale for Adolescents (SAS-A) for social anxiety, the Peer Experiences Questionnaire – Revised (PEQ-R) for peer rejection, and the Brief Fear of Negative Evaluation Scale (BFNE) for fear of negative evaluation. Data were analyzed using SPSS version 27. Pearson correlation was used to examine the relationships between the dependent and independent variables, and linear regression was conducted to assess the predictive power of peer rejection and fear of negative evaluation on social anxiety. Findings: The results revealed that both peer rejection and fear of negative evaluation had significant positive correlations with social anxiety (p < .01). Linear regression analysis showed that both independent variables significantly predicted social anxiety (p < .001), with fear of negative evaluation emerging as the stronger predictor. These findings indicate that adolescents who experience higher levels of peer rejection and who exhibit greater fear of negative evaluation are more likely to report elevated symptoms of social anxiety. Conclusion: The study highlights the importance of both interpersonal experiences and internal cognitive mechanisms in the development of social anxiety among adolescents. The findings suggest that addressing fear of negative evaluation and improving peer relationships may be key targets for early intervention and prevention strategies aimed at reducing social anxiety in school-aged youth.study aimed to examine the structural relationships between thought/action fusion, cognitive beliefs, mindfulness, and experiential avoidance with symptoms of OCD in a non-clinical population.